Task mapping and routing optimization for hard real-time Networks-on-Chip - M. Norazizi Sham Mohd Sayuti; Ridzuan F.H.M.; Abdullah Z.H. (Institute of Advanced Engineering and Science, 2024)
Indexed by SCOPUS